Pericytes promote malignant ovarian cancer progression in mice and predict poor prognosis in serous ovarian cancer patients - Sinha, D.; Chong, L.; George, J.; Schlüter, H.; Mönchgesang, S.; Mills, S.; Li, J.; Parish, C.; Bowtell, D.; Kaur, Pritinder (American Association Cancer Research, 2016)
Purpose: The aim of this study was to investigate the role of pericytes in regulating malignant ovarian cancer progression. Experimental Design: The pericyte mRNA signature was used to interrogate ovarian cancer patient datasets to determine its prognostic value for recurrence and mortality. Xenograft models of ovarian cancer were used to determine if co-injection with pericytes affected tumor growth rate and metastasis, whereas co-culture models were utilized to investigate the direct effect of pericytes on ovarian cancer cells. Pericyte markers were used to stain patient tissue samples to ascertain their use in prognosis. Results: Interrogation of two serous ovarian cancer patient datasets [the Australian Ovarian Cancer Study, n = 215; and the NCI TCGA (The Cancer Genome Atlas), n = 408] showed that a high pericyte score is highly predictive for poor patient prognosis. Co-injection of ovarian cancer (OVCAR-5 & -8) cells with pericytes in a xenograft model resulted in accelerated ovarian tumor growth, and aggressive metastases, without altering tumor vasculature. Pericyte co-culture in vitro promoted ovarian cancer cell proliferation and invasion. High αSMA protein levels in patient tissue microarrays were correlated with more aggressive disease and earlier recurrence. Conclusions: High pericyte score provides the best means to date of identifying patients with ovarian cancer at high risk of rapid relapse and mortality (mean progression-free survival time < 9 months). The stroma contains rare yet extremely potent locally resident mesenchymal stem cells—a subset of “cancer-associated fibroblasts” that promote aggressive tumor growth and metastatic dissemination, underlying the prognostic capacity of a high pericyte score to strongly predict earlier relapse and mortality.